The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s0102-05362013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Sinergism among auxins, gibberellins and cytokinins in tomato cv. Micro-Tom

Abstract: The aim of this study was to evaluate the effect of isolated and combined applications of gibberellic acid (gibberellin), indolbutyric acid (auxin) and kinetin (cytokinin) on vegetative and reproductive development of tomato test plants (Solanum lycopersicum cv. Micro-Tom), to better elucidate the interactions among these hormonal classes. The following treatments were accomplished through foliar application: GA3 (5 mg L-1); IBA (5 mg L-1); KIN (9 mg L-1); GA3 + IBA (5 mg L-1 + 5 mg L-1); GA3 + KIN (5 mg L-1 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Auxins, gibberellic acids, and cytokinins are important plant hormones that synergistically regulate cell division, cell expansion, control shoot meristem development, and stem elongation (Cato, Macedo, & Peres, ). Teng et al () investigated the effects of e[CO 2 ] on plant hormones using Arabidopsis thaliana and concluded that there was a significant increment in indole‐3‐acetic acid (one of the common plant hormones in the auxin class), gibberellic acid, zeatin riboside, dihydrozeatin riboside, and isopentenyl adenosine of the class cytokinin at e[CO 2 ].…”
Section: Impact Of Elevated [Co2] On Other Cellular Mechanisms and Itmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxins, gibberellic acids, and cytokinins are important plant hormones that synergistically regulate cell division, cell expansion, control shoot meristem development, and stem elongation (Cato, Macedo, & Peres, ). Teng et al () investigated the effects of e[CO 2 ] on plant hormones using Arabidopsis thaliana and concluded that there was a significant increment in indole‐3‐acetic acid (one of the common plant hormones in the auxin class), gibberellic acid, zeatin riboside, dihydrozeatin riboside, and isopentenyl adenosine of the class cytokinin at e[CO 2 ].…”
Section: Impact Of Elevated [Co2] On Other Cellular Mechanisms and Itmentioning
confidence: 99%
“…Accumulation of ACC oxidase is higher under e[CO 2 ] as this enzyme has an absolute requirement of [CO 2 ] for its activation, and thus contributes to high levels of ethylene production (Finlayson & Reid, 1996). It has been demonstrated that an increase in ethylene production is a key feature of accelerated growth and development in rice under e[CO 2 ] that accelerates tiller number and auxiliary bud development, potentially leading to higher grain yield (Cato, Macedo, & Peres, 2013). Teng et al (2006) Souza et al, 2008;Gupta et al, 2005;Taylor et al, 2005;Wei et al, 2013).…”
Section: Plant Hormonal Metabolism Is Influenced By Elevated [Co 2 ]mentioning
confidence: 99%
“…This is related to the fact that TOL is easily absorbed by plants and acts as an auxin synthesis regulator, through the TOL‐oxidase enzyme activity (Lebuhn et al, ). It is known that auxins are responsible for plant growth by directly influencing the cell expansion mechanism and apical and root development (Cato et al, ). TOL accumulation in leaves may have contributed to a better hormonal balance in the plant shoot by being converted into auxin, thus favouring the polar‐basipetal transport and consequently increasing the root volume and area.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points out that plant growth regulators (PGR), an organic non‐nutrient compound that may interfere with (by promoting or inhibiting) the morphological and/or physiological processes when applied at low concentrations, are extensively used in the search to achieve higher yield (Cato et al, ). Silva et al () have noted that the application of PGR, composed of auxin, cytokinin and gibberellic acid, in Phaseolus vulgaris seeds led to an increase in shoot dry matter of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Based in the results of this work it was visibly observed that there were limitations in the development of the crop; however, the data showed that the application of the treatments which utilize pyraclostrobin allow the production of floral stems, as well as the treatment with the mixture of vegetal regulators also synergistically actuated over the rose crop. It is supposed that throughout the crop cycle a regulation in the hormonal level occurred to overwhelm the stress and to alleviate the oxidative stress of the plants, such as suggested by Kanungo & Joshi (2014) when they used strobilurins, and by Cato (2013), when utilizing the vegetal regulators.…”
Section: Production (Stems Plant -1 ) Variation Source 292 Datmentioning
confidence: 99%